Summary report panel 1: The need for protocols and standards in research on underwater noise impacts on marine life - Erbe, Christine; Ainslie, M.; de Jong, C.; Racca, R.; Stocker, M. (2016)
As concern about anthropogenic noise and its impacts on marine fauna is increasing around the globe, data are being compared across populations, species, noise sources, geographic regions, and time. However, much of the raw and processed data are not comparable due to differences in measurement methodology, analysis and reporting, and a lack of metadata. Common protocols and more formal, international standards are needed to ensure the effectiveness of research, conservation, regulation and practice, and unambiguous communication of information and ideas. Developing standards takes time and effort, is largely driven by a few expert volunteers, and would benefit from stakeholders’ contribution and support.